FRBR/FRAD and Eva Verona's Cataloging Code : toward the future development of Croatian Cataloging Code - Willer, Mirna (Array, 2012)
The purpose of this article is to research the feasibility of evolving Eva Verona’s Code and Manual for Compiling Alphabetical Catalogues, the current Croatian cataloging code, into a Functional Requirements for Bibliographic Records (FRBR)/Functional Requirements for Authority Data (FRAD) structured code of rules, with the aim of assessing the direction to be taken toward development of the future national cataloging rules. The methodology used is the mapping of conceptual models FRBR and FRAD entities, attributes, and relationships to Verona’s Code of rules.